Exogenous Application of Non-mature miRNA-Encoded miPEP164c Inhibits Proanthocyanidin Synthesis and Stimulates Anthocyanin Accumulation in Grape Berry Cells - Vale, Mariana; Rodrigues, Jéssica; Badim, Hélder; Gerós, Hernâni; Conde, Artur (Frontiers in Plant Science, 2021)
Secondary metabolic pathways in grape berries are tightly regulated by an array of molecular mechanisms, including microRNA-mediated post-transcriptional regulation. As recently discovered, before being processed into mature miRNAs, the primary transcripts of miRNAs (pri-miRNAs) can encode for small miRNA-encoded peptides (micropeptides - miPEPs) that ultimately lead to an accentuated downregulation of the respective miRNA-targeted genes. Although few studies about miPEPs are available, the discovery of miPEPs reveals a new layer of gene regulation at the post-transcriptional level that opens the possibility to regulate plant metabolism without resorting to gene manipulation. Here, we identified a miPEP encoded in non-mature miR164c putatively targeting grapevine transcription factor VvMYBPA1 (miPEP164c/miPEP-MYBPA1), a positive regulator of key genes in the proanthocyanidin-biosynthetic pathway, a pathway that competes directly for substrate with the anthocyanin-biosynthetic pathway. Thus, the objective of this work was to test the hypothesis that the exogenous application of miPEP164c (miPEP-MYBPA1) can modulate the secondary metabolism of grape berry cells by inhibiting PA biosynthetic pathway while simultaneously stimulating anthocyanin synthesis. The exogenous application of miPEP164c to suspension-cultured cells from grape berry (cv. Gamay) enhanced the transcription of its corresponding non-mature miR164c, with a maximum effect at 1 µM and after a period of 10 days, thus leading to a more pronounced post-transcriptional silencing of its target VvMYBPA1. This led to a significant inhibition of the proanthocyanidin pathway, mostly via inhibition of leucoanthocyanidin reductase and anthocyanidin reductase enzymatic activities and VvLAR1 downregulation. In parallel, the anthocyanin-biosynthetic route was stimulated. Anthocyanin content was 31 % higher in miPEP164c-treated cells, in agreement with the observed upregulation of VvUFGT1 transcripts and UFGT enzyme activity levels.